(untitled) (Journal of Engineering, 2013)
In this study water quality was indicated in terms of Water Quality Index that was determined through summarizing multiple parameters of water test results. This index offers a useful representation of the overall quality of water for public or any intended use as well as indicating pollution, which are useful in water quality management and decision making. The application of Water Quality Index (WQI) with ten physicochemical water quality parameters was performed to evaluate the quality of Euphrates River water for drinking usage. This was done by subjecting the water samples collected from seven stations within Al-Anbar province during the period 2004-2010 to comprehensive physicochemical analysis. The ten physicochemical parameters included: pH value, Alkalinity (ALK), Orthophosphate (PO4-3), Nitrate (NO3-),Sulphate (SO4-2), Chloride (Cl-), Total Hardness (TH), Calcium (Ca), Magnesium (Mg), and Total Dissolved Solids (TDS). The average annual overall WQI was found to be 107.59 through the study period. The high WQI obtained is a result of the high concentrations of Orthophosphate and Magnesium which can be attributed to the various human activities taking place along the river banks. From this analysis the quality of the Euphrates River is classified as "very poor quality" ranging poor water at the river upstream near station (E1) and unsuitable for drinking at the river downstream near station (E7) with an annual minimum WQI of 89.34 in 2008 and maximum 112.44 in 2009. The present study demonstrated the application of WQI in estimating and understanding the water quality of Euphrates River. WQI appears to be promising in water quality management and a valuable tool in categorizing pollution sources in surface waters